Sustainable Environmental Solutions - Ferro, Sergio; Vocciante, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book collects research activities focused on the development of new processes to replace obsolete practices that are often highly invasive, unsustainable, and socially unacceptable.Taking inspiration from real problems and the need to face real cases of contamination or prevent potentially harmful situations, the development and optimization of 'smart' solutions, i.e., sustainable not only from an environmental point of view but also economically, are discussed in order to encourage, as much as possible, their actual implementation.